Gender Equality, Climate Change and Agriculture in the MENA region: Priorities and Possibilities - Baruah, Bipasha; Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2022)
The MENA region is both disproportionately vulnerable to compound climate fragility risks and among the most gender unequal regions in the world. Although we must be wary of over-generalizing about women’s needs and experiences across such a diverse set of geographic, ecological, cultural, socio-economic, political, and institutional contexts, the existing body of research on gender and climate change in MENA does enable us to comment reasonably certainly on what we know and what we do not know about the opportunities and challenges women experience in agriculture, the gendered effects and outcomes of climate change upon agriculture, and the roles women have played and could play in the future in adapting and building resilience to climate effects. Based on this existing scientific literature, we also identify gaps in evidence and knowledge, and make practical recommendations for future research and public policy.